Impact of digital surge during Covid-19 pandemic: A viewpoint on research and practice - De’, Rahul; Pandey, Neena; Pal, Abhipsa (International Journal of Information Management, 2020)
•We examine the digital surge during the pandemic, and after.•Prominent issues in the use of blockchains, gig economy, workplace monitoring.•Aspects of internet governance, digital payments, privacy and security.•Implications for future research and technology policy. The Covid-19 pandemic has led to an inevitable surge in the use of digital technologies due to the social distancing norms and nationwide lockdowns. People and organizations all over the world have had to adjust to new ways of work and life. We explore possible scenarios of the digital surge and the research issues that arise. An increase in digitalization is leading firms and educational institutions to shift to work-from-home (WFH). Blockchain technology will become important and will entail research on design and regulations. Gig workers and the gig economy is likely to increase in scale, raising questions of work allocation, collaboration, motivation, and aspects of work overload and presenteeism. Workplace monitoring and technostress issues will become prominent with an increase in digital presence. Online fraud is likely to grow, along with research on managing security. The regulation of the internet, a key resource, will be crucial post-pandemic. Research may address the consequences and causes of the digital divide. Further, the issues of net neutrality and zero-rating plans will merit scrutiny. A key research issue will also be the impact and consequences of internet shutdowns, frequently resorted to by countries. Digital money, too, assumes importance in crisis situations and research will address their adoption, consequences, and mode. Aspects of surveillance and privacy gain importance with increased digital usage.